Effects of Dietary Calcium and Phosphorus Levels on Growth Performance, Calcium–Phosphorus Homeostasis, and Gut Microbiota in Ningxiang Pigs - Wenzhi Liu; Cheng Zhang; Xijie Kuang; Xianglin Zeng; Jiaqi Zhang; Qiye Wang; Huansheng Yang (Life)
Optimal dietary calcium (Ca) and phosphorus (P) requirements remain undetermined for Ningxiang pigs, a valuable indigenous Chinese breed. This study conducted a continuous feeding trial with two growth phases (grower: 30–50 kg; finisher: 50–80 kg) using fixed Ca/P ratios to systematically evaluate the effects of Ca/P levels on growth performance and mineral metabolism. A total of 180 pigs per phase were allocated to four Ca/P levels. During the grower phase, a dietary regimen of 0.83% Ca/0.67% P significantly increased the average daily feed intake (ADFI), average daily gain (ADG), and apparent total tract digestibility (ATTD) of energy and P. In the finisher phase, 0.60/0.48% Ca/P showed optimal growth performance, upregulated jejunal mineral transporters (CaSR and SLC34A2), enhanced bone mineralization (metatarsal ash content), and improved intestinal morphology (duodenal and jejunal villus height, jejunal villus surface area). This regimen also selectively enriched Peptostreptococcaceae abundance, indicating improved host–microbe interactions. Based on these findings, stage-specific nutritional strategies were recommended: 0.83% Ca/0.67% P during the grower phase and 0.60% Ca/0.48% P during the finisher phase. These protocols synergistically improve microbial ecology, intestinal function, and bone metabolism, thereby maximizing the growth potential of Ningxiang pigs.